Evaluating the Competitive Ability of Durum Wheat Varieties. (1st November 2017) - Katsileros, D. A.; Hadasch, S.; Piepho, H. P.; Skaracis, G. N.
Abstract : Core Ideas: Competition of wheat varieties was assessed by growing them in neighboring plots. The competitive abilities of the varieties were categorized using a linear mixed model. Using the mixed model, we propose a measure to test the interaction of two varieties. Competitive abilities can be used to identify varieties that may be grown in a variety mixture. When two varieties are grown in neighboring plots, they compete for resources like nutrients, water, and solar energy. The performance of the two varieties under competition depends on their competitive ability, which comprises (i) the ability of a variety to withstand suppression by another variety and (ii) the ability to suppress the other variety. In this article, a linear mixed model was used to evaluate the competitive ability in terms of (i) and (ii). Furthermore, a measure to determine the synergistic effects of two competing varieties, which indicates if two competing varieties interact, is proposed. For illustration, we use yield data of six durum wheat varieties collected in trials during 2006–2007 and 2007–2008 using a split block design that provides all pairs of competing varieties. Estimating competitive abilities by the model proposed could prove helpful in exploiting the use of variety mixtures. Such mixtures were shown to be able to compete with, or even outperform, monocultures in different crops.